COMPARISON OF EFFECTS OF BIOFEEDBACK ASSISTED ISOMETRIC EXERCISE AND ELECTRICAL STIMULATION ON QUADRICEPS STRENGTH IN KNEE OSTEOARTHRITIS - Dilek Durmuş,; Ferhan Cantürk,; Gamze Alaylı, (Archives of Rheumatology, 2005)
The aim of this study was to evaluate the effects of biofeedback assisted isometric exercise and electrical stimulation program on quadriceps strength and thigh circumference measurements. Fifty women aged between 42 and 74 years old with the diagnose of knee osteoarthritis (OA) according to American College of Rheumatology (ACR) criteria participated in the study. Patients were randomized into two groups. For both groups a 20 minute therapy was applied 5 days a week. Both groups were treated for 4 weeks. The patients were evaluated before and after the treatment. 1 RM (Repetition Maximum) and 10 RM were used to evaluate muscle strength. Thigh circumference was measured 15 cm above the patella. There were statistically significant improvements in both groups in 1 RM and 10 RM values showing the improvement in muscle strength (p<0.001). Although there was no significant improvement in thigh circumference measurement in the exercise group (p>0.05), there was statistically significant improvement in thigh circumference in the ES group (p<0.05). According to our findings we conclude that both treatment protocols can be used in the treatment of knee osteoarthritis to increase the muscle strength.